Economic Development and the Church in French Canada - Ryan, S.J., William (Relations industrielles / Industrial Relations, 1966)
The author has chosen to dwell at some length of the methodology, limitations and general conclusions of his research project — his doctoral thesis presented at Harvard University. Among the more interesting findings of this research is the following : there appears to be little hard evidence that the Catholic Church exercised a significantly negative influence on the economic spurt that took place in Québec in the period 1896-1914.